From grave to glory resurrection in the New Testament : including a response to Norman L. Geisler - Harris, Murray J.; Geisler, Norman L. 1932- (Grand Rapids, MI Zondervan, 1990)
Includes bibliographical references.
Brethren writer.
Keywords: Jesus Christ -- Resurrection -- biblical teaching; Bible. N.T. -- criticism, interpretation, etc; Geisler, Norman L. -- views on resurrection in the New Testament